Implementasi Merdeka Belajar Guru Penggerak dalam Merealisasikan Pembelajaran Berbasis Kurikulum Merdeka di Sekolah Dasar - Marlina, Tuti; Soleha, Soleha (Universitas Batanghari Jambi, 2023)
Independent learning is an essential element in an independent curriculum that is driven or led by a driving teacher. The analysis in this study uses qualitative methods. The main objective is to analyze and formulate the stages in implementing independent learning for driving teachers to realize an independent curriculum. As for the independent curriculum itself, in its implementation it is dynamic, flexible and changes according to the educational needs of each school. In planning independent learning activities, this can be done by: developing a learning framework, mapping competency standards and learning assessments, mapping learning according to the Pancasila student profile, and setting a flow of learning objectives. Whereas in implementing the independent curriculum, it can carry out learning contracts between teachers and students, carry out literacy and numeracy-based learning, and apply discussion and collaboration learning methods. The orientation of learning activities in the independent curriculum is the freedom of students and teachers in carrying out learning. So that learning that is oriented towards an independent curriculum can be carried out by free, creative and innovative in accordance with the interests of students and is able to develop their talents.